Exploring Chemical Analysis - Harris D. C. Daniel (International Edition)
Shells and skeletons of marine organisms such as plankton and coratare made of calcium carbonate. The front cover shows the mineral aragonite, one of the two crystalline forms of calcium carbonate. Since 1950, the burning of fossil fuels including coal, oil, wood, and natural gas, has increased atmospheric CO, by 25%—and this number is rising every year. A similar quantity of C02 has entered the ocean. This dissolved C02 acts as an acid and has lowered the pH of the ocean by -0.1 unit so far. Continued burning of fossil fuels threatens sea life by dissolution of calcium carbonate shells and skeletons. Loss of marine life at the bottom of the food chain threatens the entire food chain. Box 11-1 in this book highlights chemical equilibrium aspects of ocean acidification.